Upaya Pengumpulan Zakat Perkebunan Kelapa Sawit oleh BAZNAS Kabupaten Dharmasraya di Nagari Sitiung - Warman, Meilita Teza; Asmadia, Tezi; Nopiardo, Widi; Emrizal, Emrizal (ZAWA: Management of Zakat and Waqf Journal, 2025)
The potential for zakat in Dharmasraya Regency is very large, especially from the oil palm plantation sector which dominates the regional economy. However, zakat collection from this sector is not optimal, especially in Nagari Sitiung, Sitiung District, which has around 402 oil palm farmers with a land area of 2,375 hectares. One of the challenges faced is the lack of understanding and lack of data collection regarding zakat obligations among oil palm farmers. This research aims to analyze the potential for zakat that can be collected from the oil palm plantation sector in Nagari Sitiung and identify the efforts made by the Dharmasraya Regency National Zakat Amil Agency (BAZNAS) in maximizing zakat collection from the oil palm plantation sector. This research uses a qualitative descriptive approach with field research methods, which involves interviews with oil palm farmers and BAZNAS amil Dharmasraya Regency, as well as documentation related to zakat potential and data on oil palm plantations in Nagari Sitiung. The data analysis techniques used include data reduction, data presentation, and drawing conclusions. Source and method triangulation techniques are used to verify the validity of the data. The research results show that the zakat potential from the oil palm plantation sector in Nagari Sitiung reaches around IDR 1,953,213,750 per year, with around 68% of farmers meeting the requirements to pay zakat. BAZNAS Dharmasraya Regency has made various efforts to maximize zakat collection, both through direct approaches (socialization, formation of UPZ, and religious studies) and indirectly (the "One Bunch of Palm Oil for the Poor" program and the use of social media). Even though these efforts have been made, several obstacles, such as limited human resources and facilities, are still challenges in expanding zakat collection from the palm oil sector.